Composites of Polypropylene Melt Blended with Synthesized Silica Nanoparticles - Zapata-Ramirez, P (2011)
Spherical and layered silica nanoparticles synthesized by the sol-gel method were melt blended with a polypropylene matrix in order to quantify their effect on thermal and mechanical behaviours of the resulting polymer composites. Transmission electron microscopy images showed that spherical nanoparticles were dispersed in the polymer matrix whereas layered particles display tactoid and agglomerated structures. By thermogravimetric analysis, it was observed that independent of the particle aspect ratio, the nanofillers render larger thermal degradation stabilization to the polymer matrix under oxidative conditions than under inert atmosphere. Noteworthy, the largest improvements were found by using spherical nanoparticles in presence of a compatibilizer. These results allow the conclusion that the physical/chemical adsorption of the volatile products on the particle surface during the oxidative degradation is the plausible mechanism behind the thermal stabilization. Tensile stress-strain tests otherwise showed that composites with spherical nanoparticles can display similar or even larger elastic modulus than composites with layered particles showing that the polymer/particle entanglement could be the mechanism for the load transfer in these nanocomposites. © 2011 Elsevier Ltd.
Keywords: Polymer-matrix composites (PMCs); Thermogravimetric analysis (TGA); Thermal properties